Growth and viability of macrophages continuously stimulated to produce nitric oxide - Zhuang, John C. (The National Academy of Sciences of the USA, 1997)
Deregulated production of nitric oxide (NO) has been implicated in the development of certain human diseases, including cancer. We sought to assess the damaging potential of NO produced under long-term conditions through the development of a suitable model cell culture system. In this study, we report that when murine macrophage-like RAW264.7 cells were exposed continuously to bacterial lipopolysaccharide (LPS) or mouse recombinant interferon-γ (IFN-γ) over periods of 21–23 days, they continued to grow, but with doubling times 2 to 4 times, respectively, longer than the doubling time of unstimulated cells. Stimulated cells produced NO at rates of 30 to 70 nmol per million cells per day throughout the stimulation period. Within 24 hr after removal of stimulant, cells resumed exponential growth. Simultaneous exposure to LPS and IFN-γ resulted in decreased cell number, which persisted for 2 days after removal of the stimulants. Exponential growth was attained only after an additional 4 days. Addition of N-methyl-l-arginine (NMA), an NO synthase inhibitor, to the medium inhibited NO production by 90% of all stimulated cells, partially reduced doubling time of cells stimulated with LPS or IFN-γ, and partially increased viability and growth rates in those exposed to both LPS and IFN-γ. However, when incubated with LPS and IFN-γ at low densities both in the presence and in the absence of NMA, cells grew at a rate slower than that of unstimulated cells, with no cell death, and they resumed exponential growth 24 hr after removal of stimulants. Results from cell density experiments suggest that macrophages are protected from intracellularly generated NO; much of the NO damaging activity occurred outside of the producer cells. Collectively, results presented in this study suggest that the type of cellular toxicity observed in macrophages is markedly influenced by rate of exposure to NO: at low rates of exposure, cells exhibit slower growth; at higher rates, cells begin to die; at even higher rates, cells undergo growth arrest or die. The ability of RAW264.7 cells to produce NO over many cell generations makes the cell line a useful system for the study of other aspects of cellular damage, including genotoxicity, resulting from exposure to NO under long-term conditions.